World Economic Outlook, April 2022. (World Economic Outlook, 2022)
The war in Ukraine has triggered a costly humanitarian crisis that demands a peaceful resolution. At the same time, economic damage from the conflict will contribute to a significant slowdown in global growth in 2022 and add to inflation. Fuel and food prices have increased rapidly, hitting vulnerable populations in low-income countries hardest. Global growth is projected to slow from an estimated 6.1 percent in 2021 to 3.6 percent in 2022 and 2023. This is 0.8 and 0.2 percentage points lower for 2022 and 2023 than projected in January. Beyond 2023, global growth is forecast to decline to about 3.3 percent over the medium term. War-induced commodity price increases and broadening price pressures have led to 2022 inflation projections of 5.7 percent in advanced economies and 8.7 percent in emerging market and developing economies-1.8 and 2.8 percentage points higher than projected last January. Multilateral efforts to respond to the humanitarian crisis, prevent further economic fragmentation, maintain global liquidity, manage debt distress, tackle climate change, and end the pandemic are essential.